2014
DOI: 10.1128/aem.01237-14
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of Swarming Motility, Biosurfactant Synthesis, and Biofilm Matrix Exopolysaccharide Production in Pseudomonas aeruginosa

Abstract: Biofilm formation is a complex process in which many factors are involved. Bacterial swarming motility and exopolysaccharides both contribute to biofilm formation, yet it is unclear how bacteria coordinate swarming motility and exopolysaccharide production. Psl and Pel are two key biofilm matrix exopolysaccharides in Pseudomonas aeruginosa. This opportunistic pathogen has three types of motility, swimming, twitching, and swarming. In this study, we found that elevated Psl and/or Pel production reduced the swar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 47 publications
2
81
0
1
Order By: Relevance
“…These results indicated that high iron levels inhibited the expression of RhlI/RhlR and RhlAB in order to reduce the rhamnolipid biosynthesis. This revealed another way that iron stimulated Psl production in P. aeruginosa at the posttranslational level because the decrease in rhamnolipid production can increase Psl production (57).…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that high iron levels inhibited the expression of RhlI/RhlR and RhlAB in order to reduce the rhamnolipid biosynthesis. This revealed another way that iron stimulated Psl production in P. aeruginosa at the posttranslational level because the decrease in rhamnolipid production can increase Psl production (57).…”
Section: Resultsmentioning
confidence: 99%
“…The negative influence of mixture consist of fengycin and surfactin produced by B. subtilis and B. licheniformis on E. coli and S. aureus adhesion was observed by Rivardo et al [23]. Wang et al [24] suggested that bacteria coordinate i.e. biosurfactants and exopolysaccharide production which mediated biofilm formation by mechanism in which competition for common sugar precursors mannose-1-phosphate (Man-1-P) and glucose-1-phosphate (Glc-1-P) used for both expopolysaccharides and rhamnolipids synthesis serves as control of the bacterial motility, biofilm formation and surfactants production.…”
Section: Eko-dok 2017mentioning
confidence: 90%
“…31 In addition, studies have reported that nutritional condition, viscosity, and rhamnolipids contribute to swarming motility. 31,36 Pseudomonas aeruginosa cells may adjust to make an environment more favorable, then exert their virulence. The role of flagella involves not only movement for adhesion on corneal epithelium, but may also involve activation of immunity.…”
Section: Discussionmentioning
confidence: 99%